Design and Analysis of Closed Power Flow Bevel Gear Test Bench and Transmission Gearbox - Wei Bingyang; Wang Junheng; Deng Xiaozhong; Liu Zhongming; Meng Lingxian (Jixie chuandong)
The background and significance of gear test detection platform and basic database construction are introduced,and a structural scheme of bevel gear closed power flow durability test bench including the composition and system function is proposed. The 3 D model of constant speed cylindrical gearbox is established by using Solid Works 3 D software,the statics and modal of the box are analyzed according to the actual working load of the test bench by finite element method. The maximum stress,deformation and natural frequency of the box and the corresponding vibration mode are obtained,and the result of the strength check of meshing gears verify the constant speed cylindrical gearbox meeting design requirement.